The New Division of Labor : How Computers Are Creating the Next Job Market - Levy, Frank, 1941-; Murnane, Richard J. (Book collections on Project MUSE., 2004)
"As the current recession ends, many workers will not be returning to the jobs they once held -- those jobs are gone. In The New Division of Labor, Frank Levy and Richard Murnane show how computers are changing the employment landscape and how the right kinds of education can ease the transition to the new job market. The book tells stories of people at work -- a high-end financial advisor, a customer service representative, a pair of successful chefs, a cardiologist, an automotive mechanic, the author Victor Hugo, floor traders in a London financial exchange. The authors merge these stories with insights from cognitive science, computer science, and economics to show how computers are enhancing productivity in many jobs even as they eliminate other jobs -- both directly and by sending work offshore. At greatest risk are jobs that can be expressed in programmable rules -- blue collar, clerical, and similar work that requires moderate skills and used to pay middle-class wages. The loss of these jobs leaves a growing division between those who can and cannot earn a good living in the computerized economy. Left unchecked, the division threatens the nation's democratic institutions. The nation's challenge is to recognize this division and to prepare the population for the high-wage/high-skilled jobs that are rapidly growing in number -- jobs involving extensive problem solving and interpersonal communication. Using detailed examples -- a second grade classroom, an IBM managerial training program, Cisco Networking Academies -- the authors describe how these skills can be taught and how our adjustment to the computerized workplace can begin in earnest. Book jacket."--Jacket